2016
DOI: 10.4028/www.scientific.net/kem.721.245
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Inflammatory Cytokines and Antimicrobial Peptides after Composite Material Implantation and Contamination with Bacterial Culture

Abstract: As biomaterial implantation is a traumatic process, especially if the implanted object becomes contaminated by bacteria, it can cause a significant increase in the production of inflammatory cytokines. An increase in the level of inflammatory cytokines can be used as a marker of biomaterial associated infection (BAI) in surrounding tissues. To prevent BAI and production of inflammatory cytokines, biomaterials with antibiotics should be used, in particular biomaterials with prolonged release of antibiotics. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Moreover, IL-1 and TNF-α production in human monocytes increased by the addition of LPS in the presence of biomaterials [57]. Pro-inflammatory IL-1β, IL-6, and TNF-α cytokines increased in patients bearing hip prosthetics after infection with coagulase-negative staphylococci [58]. The level of inflammatory cytokines IL-10 and TNF-α increased when biomaterials were infected with Staphylococcus epidermidis or Pseudomonas aeruginosa [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IL-1 and TNF-α production in human monocytes increased by the addition of LPS in the presence of biomaterials [57]. Pro-inflammatory IL-1β, IL-6, and TNF-α cytokines increased in patients bearing hip prosthetics after infection with coagulase-negative staphylococci [58]. The level of inflammatory cytokines IL-10 and TNF-α increased when biomaterials were infected with Staphylococcus epidermidis or Pseudomonas aeruginosa [59].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory IL-1β, IL-6, and TNF-α cytokines increased in patients bearing hip prosthetics after infection with coagulase-negative staphylococci [ 57 ]. The level of inflammatory cytokines IL-10 and TNF-α increased when biomaterials were infected with Staphylococcus epidermidis or Pseudomonas aeruginosa [ 58 ]. The current study observed a decrease in the systemic expression of IL-2 with single or dual species infections with or without implants.…”
Section: Discussionmentioning
confidence: 99%
“…The release of b-defensin-2 is stimulated by inflammatory cytokines: TNF-a and IL-1, and P. aeruginosa (Harder et al, 2001;Lai et al, 2010;Skadins et al, 2017). Betadefensin-2 is also active against S. epidermidis, a representative of the normal microbiota (Lai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since the most common causative agents of BAI are bacteria, antibacterial coatings are also considered. Such local antimicrobial coatings have a number of benefits, for example, a reduced risk of side effects that is associated with the use of systemic antimicrobials, such as dysbacteriosis, which is one of the most common causes of fungal infections (Goodman et al, 2013;Skadins et al, 2017).…”
Section: Discussionmentioning
confidence: 99%